Composite administrative procedures in the European Union - Christina Eckes; Raffaele D'Ambrosio (European Central Bank (ECB), 2020)
The two contributions in this legal working paper discuss the various aspects of composite administrative procedures in the context of both Single Supervisory Mechanism (SSM) and Single Resolution Mechanism (SRM) decision-making procedures. It addresses the definition of such procedures, their relevance in the SSM and SRM context, the allocation of powers in such procedures, differences between composite procedures in the SSM and SRM spheres and differences between composite procedures and mere cooperation or exchange of information procedures. They were originally presented at the ECB legal colloquium on 'Composite administrative procedures in the European Union', which took place in Frankfurt am Main in 2020. [...] The second paper considers what falls within the category of actual composite procedures and focuses on composite procedures within the SSM and the SRM, as well as on those composite procedures involving both (national and Union) supervisory and resolution authorities. Subsequently, the paper turns to a number of problems related to the interpretation of certain specific rules regarding SSM and SRM procedures. In particular, the author addresses: (a) the scope of the protection granted to due process rights in the two different systems, as a result of the different balance of interests at stake; (b) the powers that the ECB and the SRB enjoy, when necessary, to remedy at an early stage any prejudicial consequences that may arise from the national phase; and (c) the side effects of the allocation of jurisdiction between the Court of Justice of the European Union (CJEU) and the national courts.
Keywords: K; G2; G21; K2; K23; 330; European Central Bank; composite administrative procedures; SingleSupervisory Mechanism (SSM); Single Resolution Mechanism (SRM); Due processrequirements; national competent authorities (NCAs); national resolution authorities(NRAs); the Single Resolution Board (SRB); procedural and defence rights; legalprofessional privilege; the privilege against self-incrimination; the right to be heard; national punitive proceedings; admissibility in national proceedings of materialsgathered by Union bodies; punitive and non-punitive; allocation of jurisdiction betweenthe Court of Justice of the European Union (CJEU) and the national courts